2014
DOI: 10.1002/acn3.84
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory activity of interferon‐beta

Abstract: Multiple sclerosis (MS) is a complex disorder of the central nervous system that appears to be driven by a shift in immune functioning toward excess inflammation that results in demyelination and axonal loss. Beta interferons were the first class of disease-modifying therapies to be approved for patients with MS after treatment with this type I interferon improved the course of MS on both clinical and radiological measures in clinical trials. The mechanism of action of interferon-beta appears to be driven by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 67 publications
1
86
1
4
Order By: Relevance
“…Their data clearly showed that regular vitamin D intake compared with no supplementation during the first year of life was associated with an 88% risk reduction of type 1 diabetes mellitus in later life [39]. There is substantial evidence from studies with nonobese diabetic mice that vitamin D deficiency in early life accelerates the appearance of the symptoms of autoimmune diabetes mellitus and that conversely 1,25-hydroxy vitamin D can prevent the development of the disease [7,40]. Even children who received vitamin D irregularly had an 84% lower risk than those with no supplementation.…”
Section: Type I Diabetes Mellitusmentioning
confidence: 95%
“…Their data clearly showed that regular vitamin D intake compared with no supplementation during the first year of life was associated with an 88% risk reduction of type 1 diabetes mellitus in later life [39]. There is substantial evidence from studies with nonobese diabetic mice that vitamin D deficiency in early life accelerates the appearance of the symptoms of autoimmune diabetes mellitus and that conversely 1,25-hydroxy vitamin D can prevent the development of the disease [7,40]. Even children who received vitamin D irregularly had an 84% lower risk than those with no supplementation.…”
Section: Type I Diabetes Mellitusmentioning
confidence: 95%
“…Among the current MS drugs, interferon (IFN)-b was the first marketed (Jacobs et al 1996). IFNb exerts its therapeutic function in part through anti-viral, anti-proliferative, and, particularly, immunomodulatory actions (Kasper & Reder 2014). Subsequently, glatiramer acetate was introduced as a MS drug, which affects antigen presentation and cytokine balance (Caporro et al 2014).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Unter der Therapie sollten Blutbild-und Leberwertkontrollen sowie Bestimmung des Kreatinins im ersten Jahr in 3-monatigen Abständen durchgeführt werden. IFN-β ist ein rekombinant hergestelltes Glykoprotein, welches unter physiologischen Bedingungen in der Immunantwort auf Virusinfektionen von Zellen des angeborenen Immunsystems produziert wird [33,51,91]. Die physiologische Funktion von IFN-β macht das häufi-ge Auftreten grippeähnlicher Nebenwirkungen, insbesondere zu Beginn der Therapie, verständlich.…”
Section: Praktisches Vorgehenunclassified